Clinical Characteristics and Treatment of Middle-Aged and Elderly Patients with IBD in Shanghai, China - Mi L; Wang K; Yao J; Ma J; Chen YW; Zeng Q; Liu K (International Journal of General Medicine, 2024)
Lin Mi,1,2 Ke Wang,3 Jianfeng Yao,1 Jianxia Ma,1 Yuan-Wen Chen,1 Qinglian Zeng,1 Kangwei Liu1 1Department of Gastroenterology, Huadong Hospital, Fudan University, Shanghai, 200040, People’s Republic of China; 2Department of General Medicine, Huadong Hospital, Fudan University, Shanghai, 200040, People’s Republic of China; 3Department of Gastroenterology, Jinan Third People’s Hospital, Jinan, Shandong Province, 250132, People’s Republic of ChinaCorrespondence: Jianfeng Yao; Jianxia Ma, Department of Gastroenterology, Huadong Hospital, Fudan University, NO. 221 West Yan’an Road, Shanghai, 200040, People’s Republic of China, Tel +8602162483180, Email yjf1966@126.com; yz_mjx@163.comAim: In order to better understand the incidence of IBD in China, we conducted a retrospective study to analyze the clinical information of IBD patients in Shanghai, China.Methods: From January 2014 to December 2021, patients diagnosed with IBD and hospitalized were enrolled. The demographic, clinical features, symptoms, laboratory tests and treatment data of the patients were retrospectively analyzed.Results: This study included 454 patients with UC and 333 patients with CD. The rate of hospitalization for IBD showed an escalating trend throughout the period, the number of hospitalizations was significantly higher in CD patients than in UC patients. The male patients had more complications than the female patients (p < 0.05). Definitive diagnosis of IBD in older patients was difficult (p < 0.05), and misdiagnosis was common. The incidence of complications and extraintestinal manifestations in elderly IBD patients was lower, but the incidence of intestinal obstruction was higher (p < 0.05). There was a significant correlation between the disease activity grades of IBD and fibrinogen, hemoglobin, albumin. Elderly IBD patients presented with lower rates of immunosuppressant, biologics, surgery or enteral nutrition.Conclusion: This study analyzed the incidence, characteristics and treatment of IBD patients in Shanghai, and provided evidence-based evidence for doctors to more effectively diagnose and treat IBD in the future.Keywords: inflammatory bowel disease, ulcerative colitis, Crohn’s disease, clinical features, treatment